Female Honor Killing: The Role of Low Socio-Economic Status and Rapid Modernization - Dayan, Hava (Journal of interpersonal violence, 2021)
Female honor killing is a particular form of femicide, where the killing of a woman is perpetrated by a member or members of her family who do not approve of her social behavior in general and her sexual behavior in particular. The study of female honor killing tends to focus on a cultural examination of honor cultures yet lacks exploration of possible social factors that may influence such gendered killing. Possible links between female honor killing incidence and various social factors, among them poverty, low social status, and rapid modernization, were recently postulated, however empirical validation of these hypotheses has yet to be thoroughly explored. This article offers empirical observations of an explorative nature of social factors that may play a role in the frequency of female honor killing. The research’s methodological design distinguishes between the various Arab subgroups in Israel along their correlated ingrained social characteristics and offers a comparative empirical analysis obtained from nation-based data on female honor killings among the various Arab subgroups (excluding the West Bank, Gaza, and East Jerusalem) during a 6-year period (2010-2015). The research is based on a secondary analysis of data extrapolated from media surveillance. A total of 58 eligible cases were found and comprised the research sample. Frequency analysis of femicide events and victims was performed for each Arab subgroup. Despite the small number of cases and the research’s explorative and tentative nature, it provides preliminary empirical indications of possible links between female honor killing frequency and social factors such as low economic status and rapid modernization. The article’s novel empirical indications may be of great relevance to societies currently facing the challenge of assimilating a growing number of Arab and Muslim social groups.